2022
DOI: 10.3390/agronomy12030629
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Two Species of Leucaena on In Vitro Rumen Fermentation, Methane Production and Post-ruminal Protein Supply in Diets Based on Urochloa hybrid cv. Cayman

Abstract: This study evaluates the effects of the inclusion of two different Leucaena species as a source of condensed tannins based on in vitro fermentation, methane production and post-ruminal protein supply in a diet based on Urochloa hybrid cv. Cayman CIAT BR02/1752 grass. Under in vitro conditions, Leucaena leucocephala CIAT 17263 and Leucaena diversifolia ILRI 15551 were incubated in two proportions (25% and 50% w/w) with Cayman grass and with/without polyethylene glycol as a tannin-binder. The results show that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This influence seemed particularly strong in the case of L. diversifolia fed at 30% of DM. In fact, it has been reported that whereas L. diversifolia reduced methane production, L. leucocephala did not [30]. Nonetheless, in other studies, the addition of L. leucocephala to a diet of Star grass increased DMI and productivity without increasing methane emission [31,32].…”
Section: Discussionmentioning
confidence: 86%
“…This influence seemed particularly strong in the case of L. diversifolia fed at 30% of DM. In fact, it has been reported that whereas L. diversifolia reduced methane production, L. leucocephala did not [30]. Nonetheless, in other studies, the addition of L. leucocephala to a diet of Star grass increased DMI and productivity without increasing methane emission [31,32].…”
Section: Discussionmentioning
confidence: 86%
“…Feeding is a critical aspect of dairy cow production since it impacts the capacity of the cattle to manifest their natural abilities. The quality of the diet of dairy cattle is affected through its chemical content and also by how dairy cattle consume it. Insights on how dairy cattle use their feeds, such as feed digestibility, can help ration formulation be more accurate when dairy cow output is forecast.…”
Section: Introductionmentioning
confidence: 99%